PENGARUH PRICE DISCOUNT, MOTIVASI BELANJA HEDONIS, SHOPPING LIFESTYLE TERHADAP IMPULSE BUYING PADA PRODUK DAZZLE ME - Ayu Putri Pangestu; Yayan Hendayana; Sri Wulandari (Jurnal Riset Multidisiplin Edukasi, 2026)
The Influence of Price Discount, Hedonic Shopping Motivation, and Shopping Lifestyle on Impulse Buying of Dazzle Me Products (Case Study of Students of the Faculty of Economics and Business, Bhayangkara University, Jakarta Raya). This study employed a quantitative research method using a survey approach. Data were collected through questionnaires distributed to respondents who had previously purchased Dazzle Me products. The data were analyzed using SmartPLS 4 through outer model and inner model evaluations. The outer model assessment was conducted to examine the validity and reliability of the research instruments, while the inner model assessment was used to evaluate the relationships among the research variables. This study is expected to contribute to the development of marketing management knowledge, particularly in the field of consumer behavior, and to provide practical insights for companies in designing more effective marketing strategies to stimulate impulse buying behavior among consumers.